EVALUASI PENGGUNAAN BIAYA TRANSPORTASI DALAM MEMINIMUMKAN BIAYA PENGIRIMAN CARTON BOX PADA PT. PINDODELI PULP AND PAPER MILLS 2 KARAWANG - Cinta Chantika Suryana Rachman; Wanta Wanta; Dwi Epty Hidayaty (Politeknik Negeri Ambon, 2025)
Introduction: The development of technology, including transportation, continues rapidly, many companies are trying to survive and thrive in the midst of intense competition, especially in managing the cost of shipping goods. This study aims to evaluate the use of transportation costs in minimizing the cost of shipping carton boxes at PT Pindo Deli Pulp and Paper Mills 2 Karawang. Methods: This study uses a quantitative descriptive method with mathematical model analysis calculating the average contract car transportation costs, to compare more efficient transportation costs, such as the use of contract car vehicles and delivery route optimization. The data used includes shipping cost reports and contract car usage for the period 2022 - 2024. Results: The results show that the rental cost in 2024 is more effective than the rental cost in 2022 and 2023. The application of the contract car method has great potential to reduce shipping costs with route optimization and effective vehicle usage. The implication of this research is that companies need to optimize and ensure the use of leased vehicles is used properly. Keywords: Financial Management, Shipping Cost, Contract Car Transportation Cost Efficiency